The Kinesin Adaptor Calsyntenin-1 Organizes Microtubule Polarity and Regulates Dynamics during Sensory Axon Arbor Development - Lee, Tristan J.; Lee, Jacob W.; Haynes, Elizabeth M.; Eliceiri, Kevin W.; Halloran, Mary C. (Frontiers in Cellular Neuroscience, 2017)
Axon growth and branching, and development of neuronal polarity are critically dependent on proper organization and dynamics of the microtubule (MT) cytoskeleton. MTs must organize with correct polarity for delivery of diverse cargos to appropriate subcellular locations, yet the molecular mechanisms regulating MT polarity remain poorly understood. Moreover, how an actively branching axon reorganizes MTs to direct their plus ends distally at branch points is unknown. We used high-speed, in vivo imaging of polymerizing MT plus ends to characterize MT dynamics in developing sensory axon arbors in zebrafish embryos. We find that axonal MTs are highly dynamic throughout development, and that the peripheral and central axons of sensory neurons show differences in MT behaviors. Furthermore, we show that Calsyntenin-1 (Clstn-1), a kinesin adaptor required for sensory axon branching, also regulates MT polarity in developing axon arbors. In wild type neurons the vast majority of MTs are directed in the correct plus-end-distal orientation from early stages of development. Loss of Clstn-1 causes an increase in MTs polymerizing in the retrograde direction. These misoriented MTs most often are found near growth cones and branch points, suggesting Clstn-1 is particularly important for organizing MT polarity at these locations. Together, our results suggest that Clstn-1, in addition to regulating kinesin-mediated cargo transport, also organizes the underlying MT highway during axon arbor development.